2012
DOI: 10.1074/jbc.m111.308965
|View full text |Cite
|
Sign up to set email alerts
|

Homeobox Protein HB9 Binds to the Prostaglandin E Receptor 2 Promoter and Inhibits Intracellular cAMP Mobilization in Leukemic Cells

Abstract: Background: HB9 is highly expressed in translocation t(7;12) positive infant AML. Results: HB9 binds to the PTGER2 promoter, down-regulates PTGER2 gene expression and subsequently represses cAMP synthesis in hematopoietic cells. Conclusion: Expression of HLXB9 represses PTGER2 mediated signaling. Significance: First molecular report of HB9-dependent target gene regulation in hematopoietic cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 37 publications
2
36
0
Order By: Relevance
“…These studies suggested a link between HLXB9 over-expression and leukaemogenesis [ 23 ]. Other authors reported a relatively low HLXB9 expression in normal bone marrow by real time quantitative PCR (RT-Q-PCR) and did not observe HLXB9 expression in healthy CD34-positive bone marrow cells, but described increased levels in the bone marrow of leukaemia patients with the t(7;12) rearrangement [ 6 , 24 ]. Observations from our group and by others confirmed elevated HLXB9 expression in t(7;12) leukaemias as well as in some patients with acute myeloid leukaemia with chromosomal abnormalities other than the t(7;12) [ 20 , 25 ].…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies suggested a link between HLXB9 over-expression and leukaemogenesis [ 23 ]. Other authors reported a relatively low HLXB9 expression in normal bone marrow by real time quantitative PCR (RT-Q-PCR) and did not observe HLXB9 expression in healthy CD34-positive bone marrow cells, but described increased levels in the bone marrow of leukaemia patients with the t(7;12) rearrangement [ 6 , 24 ]. Observations from our group and by others confirmed elevated HLXB9 expression in t(7;12) leukaemias as well as in some patients with acute myeloid leukaemia with chromosomal abnormalities other than the t(7;12) [ 20 , 25 ].…”
Section: Reviewmentioning
confidence: 99%
“…These would shed some light on the pathways triggered by this chromosomal rearrangement. The only report to date to explore possible targets for HB9 (the transcription factor coded by the HLXB9 gene) in haematopoietic cells was performed on the HL-60 myeloid cell line using ChiP-on-chip and expression profiling analyses [ 24 ]. This study describes binding of HB9 to the prostaglandin E receptor 2 ( PGTER2 ) promoter resulting in down-regulation of PGTER2 and consequent reduction of intracellular cAMP level.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…ChIP-on-chip studies have been undertaken to explore specific pathways of HLXB9 involvement in order to identify possible targets for this transcription factor [18]. These have shown that the latter binds to the promoter of the prostaglandin E receptor 2 gene ( PTGER2 ) and decreases its expression.…”
Section: Introductionmentioning
confidence: 99%
“…HLXB9 is a gene of 12,801 bp, composed of 3 exons, and the corresponding protein is a transcription factor, HB9, of 401 amino acids [Harrison et al, 1994;Wildenhain et al, 2012]. During development, HB9 controls pancreas and motoneuronal differentiation [Arber et al, 1999;Harrison et al, 1999].…”
Section: Concettamentioning
confidence: 99%